Peluang Dan Tantangan Pembiayaan Online Syariah Dalam Menghadapi Pinjaman Online Ilegal - Muh. Arafah (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2022)
This study aims to show the opportunities and challenges of Islamic online financing in dealing with illegal online loans favoured by the public. The research method uses literature studies from journals, online news, and other reading materials. The study results found Islamic online financing opportunities in dealing with illegal online loans. Indonesia has a Muslim majority population, high internet users, the issuance of fatwa number 117/DSN-MUI/II/2018, and the spread of bad interest-based online loans. Meanwhile, the challenges of Islamic online financing in dealing with illegal online loans are the low level of Islamic financial literacy, access for micro, small and medium enterprises (MSMEs) to obtain financing to the banking sector is still low, and online-based security challenges. This research can be used to reference Islamic financing and complement existing theories.